Soil Moisture and pH Monitoring System with a Flexible Monopole Antenna Based on IoT for Agricultural Applications - Akbar Izulhaq Izulhaq; Nurhayati; Hesti Khuzaimah Nurul Yusufiyah; Sayyidul Aulia Alamsyah (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2026)
This study aims to address the limitations of manual monitoring in the agricultural sector by designing an Internet of Things (IoT)- based soil moisture and pH monitoring system. The primary focus of this study is the integration of a flexible monopole antenna made of Polydimethylsiloxane (PDMS) to extend the range of data transmission on the ESP32 Wroom-U microcontroller. Using the Research and Development (R&D) method, the antenna was designed for a 2.4 GHz frequency, with simulation results showing a return loss of -14.69 dB and a VSWR of 1.45. Field test results prove that the use of a flexible external antenna can increase transmission range up to 521.59 meters, or 17 times farther than a standard antenna. The IoT system successfully transmitted sensor data to the ThingSpeak platform in real-time every 15 to 30 seconds with stable connectivity. Implementation in rice fields demonstrated the system’s accuracy in reading soil conditions and its effectiveness in operating automatic irrigation pumps. This research provides an efficient and adaptive communication infrastructure solution for the development of smart farming.